Chloroform extract of cucumber peels for Mild steel prevention in 0.5 M NaCl - Johari S.; Jaiswal A.; Sharma R.; Kumar A.; Ji G.; Prakash R. (My University, 2025)
Waste natural material has attracted the attention of many researchers and scientists for its use as a corrosion inhibitor due to their efficiency, economic cost and high biodegradability. In present report, the effect of chloroform extract of cucumber peel (CCE) is studied as natural, low cost and effective coating protection of Mild Steel (MS) in chloride (0.5 M NaCl) solutions. Characterization of CCE is performed by UV-visible (UVS) and Fourier transform infrared (FTIR) spectroscopy. Corrosion testing of MS and CCE coated MS are done in 0.5 M NaCl by open circuit potential (OCP) curves, electrochemical impedance spectroscopy (EIS) and Tafel polarization curves (TPC). Surface morphology was seen and analyzed by Field emission Scanning electron microscopy (FESEM). It is depicted from this work that CCE can effectively suppress MS corrosion in 0.5 M NaCl. © 2023 Elsevier Ltd. All rights reserved.